Validity and reliability of a visual scoring method for masticatory ability using test gummy jelly. (3rd April 2012) - Nokubi, Takashi; Yoshimuta, Yoko; Nokubi, Fukuko; Yasui, Sakae; Kusunoki, Chie; Ono, Takahiro; Maeda, Yoshinobu; Yokota, Kazunori
<x xml:space="preserve">Abstract</x> Background: For quantitative evaluation of masticatory ability of the elderly patients, there should be a simple and reliable method without special techniques and instruments. Objective: The purpose of this study was to examine the validity and reliability of a visual scoring method for assessing masticatory performance. Materials and Methods: A 10‐stage scale for visually scoring was rated based on the range of the glucose concentration dissolved from comminuted jelly. Photographic images of comminuted jellies were produced as a standard material for each score. Fifty subjects were recruited as raters who graded the visual score for 50 photographic images of comminuted jellies on the screen of a lap‐top three times in random order. Results: There were strong correlations (rs = 0.911– 0.981, Spearman's rank coefficient) between the actual scores determined from the glucose concentration and the visual scores graded by subjects in all three measurements. The intraclass correlation coefficients (ICCs) of the inter‐rater reliability and the ICCs of the intra‐rater reliability of the visual scoring ranged from 0.946 to 0.947 and from 0.860 to 0.987 in three measurements, respectively. Conclusions: These results indicated that the visual scoring method was valid and reliable for evaluation of masticatory performance.